2014
DOI: 10.1037/xan0000014
|View full text |Cite
|
Sign up to set email alerts
|

Scene gist categorization by pigeons.

Abstract: Scene gist categorization in humans is rapid, accurate, and tuned to the fundamental statistical regularities in the visual world. However, no studies have investigated whether scene gist categorization is a general process shared across species, or whether it may be influenced by species-specific adaptive specializations relying on specific low-level scene statistical regularities of the environment. Although pigeons form many types of categorical judgments, little research has examined pigeons' scene categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
1
5
1
Order By: Relevance
“…Although the survival of high-level information under crowding has also been found with stimuli of words 22 , 23 and digital numbers 26 , their stimuli were presented at only half of the eccentricity of our study and even less than half of the eccentricity of studies using faces and social actions as stimuli 3 , 24 , 62 . Thus, the present study together with others 36 , 48 , 60 , 63 seems to indicate the specificity of scene gist in visual processing, probably like the specificity of faces in visual processing 54 . Brain imaging studies have shown that the contextual information in scenes consistently activates the parahippocampal place area (PPA) and retrosplenial cortex (RSC) 65 69 , suggesting a possible gist-specific pathway involving PPA and ROC for the perception of scene gist.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although the survival of high-level information under crowding has also been found with stimuli of words 22 , 23 and digital numbers 26 , their stimuli were presented at only half of the eccentricity of our study and even less than half of the eccentricity of studies using faces and social actions as stimuli 3 , 24 , 62 . Thus, the present study together with others 36 , 48 , 60 , 63 seems to indicate the specificity of scene gist in visual processing, probably like the specificity of faces in visual processing 54 . Brain imaging studies have shown that the contextual information in scenes consistently activates the parahippocampal place area (PPA) and retrosplenial cortex (RSC) 65 69 , suggesting a possible gist-specific pathway involving PPA and ROC for the perception of scene gist.…”
Section: Discussionsupporting
confidence: 82%
“…Support for this proposal comes from studies showing that human can extract facial expression 24 , 25 , social action 62 and scene gist (the current study) under crowding. Furthermore, rapid categorization of scene gist can even be completed by pigeons 63 . This cross-species consistency provides further support for the idea that rapid representation of scene gist is an adaptive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, it is important to acknowledge that the results we have found are, as in all studies of categorization, determined to a certain degree by the diagnosticity of the information available in our scenes for the specific category sets we used. A good example of this is the fact that a follow-up study to the current experiments, done with pigeons (Kirkpatrick, Sears, Hansen, & Loschky, 2014), did a similar imagestatistical analysis to that reported in Experiment 1 and, contrary to the results of the current study, showed greater scene-category discrimination for aerial views than terrestrial views. However, that experiment only included two scene categories: coasts and mountains.…”
Section: Discussioncontrasting
confidence: 43%
“…Pigeons are capable of learning categories comprising natural objects (Herrnstein and Loveland, 1964 ; Herrnstein et al, 1976 ; Herrnstein and De Villiers, 1980 ; Bhatt et al, 1988 ; Aust and Huber, 2001 , 2002 ) human-made objects (Bhatt et al, 1988 ; Wasserman et al, 1988 ; Lazareva et al, 2004 , 2006 ), scene gist (Kirkpatrick et al, 2014 ), cartoons (Matsukawa et al, 2004 ), human face identity (Soto and Wasserman, 2011 ), gender (Troje et al, 1999 ; Huber et al, 2000 ) and emotional expression (Jitsumori and Yoshihara, 1997 ), and even paintings from different artists (Watanabe et al, 1995 ; Watanabe, 2001 ).…”
Section: Behavioral Research On Object Categorization By Pigeonsmentioning
confidence: 99%
“…Still, the evidence suggests a specialized mechanism for “holistic” face processing in people and other primates, which is not present in birds. It is also likely that birds have evolved specialized mechanisms of visual categorization; for example, flight might have had an important impact on birds’ evolved ability to categorize scenes from different perspectives (Kirkpatrick et al, 2014 ).…”
Section: The Evolution Of Mechanisms Of Object Recognition In Vertebrmentioning
confidence: 99%